Multidisciplinary intervention to improve albuterol inhaler utilization among patients with asthma. (2nd January 2017) - Delate, Thomas; Rader, Nathan; Jenkins, Daniel W.; Lowe, Ryan
ABSTRACT: Objective: The goal of this study was to examine the impact of a multidisciplinary intervention designed to improve appropriate albuterol inhaler utilization among patients with asthma. Methods: This was a pre–post retrospective analysis. The study intervention included written information sent directly to patients, educated prescribers, and enhanced pharmacist training on appropriate albuterol inhaler utilization. Eligible study patients had a diagnosis of asthma and purchased at least two albuterol inhalers between 07/12/2012 and 06/30/2013 (pre-period) and 7/01/2013 to 06/30/2014 (post-period). The primary outcome was a comparison between study periods of the count of albuterol inhalers purchased per patient per month (PPPM). Results: The median age of included patients was 41 years, 53% were females, and allergic rhinitis was the most common comorbidity. The median albuterol inhalers purchased PPPM decreased from 0.60 (interquartile range [IQR] = 0.39–0.87) to 0.37 (IQR = 0.26-0.53) from the pre- to post-period ( p < 0.001). The proportion of patients with at least one systemic corticosteroid purchase decreased (36% vs. 31%) and >1 albuterol inhaler purchased on the same day increased (3.1% vs. 5.7%) from the pre- to post-period ( p < 0.001). Numerically, the proportion of participants who experienced an acute asthma exacerbation decreased and asthma controller inhalers purchased PPPM increased but these did not reach statistical significance (both p > 0.05). Conclusions: A multidisciplinary approach to increasing appropriate albuterol inhaler use was associated with a decrease in albuterol inhalers purchased PPPM while not increasing acute asthma exacerbations. Future study is needed to evaluate patient perspectives on this intervention and assess its economic impact.